Altemeier’s Procedure, an Easy Solution for Rectal Prolapse - Khalil, Mohammad Ibrahim; Alam, ABM Khurshid; Jahan, Sharker Kamrun; Saleh, Abu Zaffor (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Rectal prolapse is an embarrassing clinical condition. Most of the time patients get emergency hospital admission. Full thickness rectal prolapse demands surgical treatment. Many surgical procedures and techniques were described but none is adopted as standard. It is challenging to choose appropriate surgical procedure in the emergency situations as many patients come after trial of reduction and maltreatment. We have treated 64 patients of full thickness rectal prolapse by Altemeier’s procedure in emergency admissions. This study was designed to observe the outcomes of Altemeier’s procedure (perineal proctosigmoidectomy) in full thickness rectal prolapse as emergency surgery. Methods: This prospective study was done in Dhaka Medical College Hospital and Cumilla Medical College Hospital over the period of January 2013 to July 2018. Total 64 patients were included in this study. Alteimer’s procedure was done in all patients. Patients were followed up on 2 weeks, 1 month, 3months, 6 months and 1 year. Patients were evaluated by complain of pain, per rectal bleeding, mucous discharge, bowel movement and incontinence. Postoperative data was collected and evaluated. Results: Reduction was achieved in all patients and they were satisfied about their prolapse correction. Two patients needed blood transfusion and laparotomy. Anastomotic disruption and bleeding from the mesenteric vessels were found on laparotomy. All patients had improved evacuation as assessed by history of satisfactory evacuation. No recurrence was reported during the follow up period. Gas and liquid incontinence were noted in 3 patients who improved with sphincter exercise within 3 months. Conclusion: In our series, we found Altemeier’s procedure is safe, effective for complete rectal prolapse specially in emergency situation and can be done under regional anesthesia. J Bangladesh Coll Phys Surg 2022; 40: 229-232